An open-source, generic, environmental model for chemical fate and transport analysis in multi-media systems. (May 2018) - Little, Keith W.; Parks, Aaron B.; Lillys, Theodore P.
Abstract: A new, open-source, software tool, the Generic Environmental Model (GEM) is summarized and illustrated herein. The GEM is a numerical approach to solving the classical, advective-dispersive, partial differential equations describing chemical fate and transport in environmental media. Its generic capabilities are due to the flexible compartment approach for spatial discretizations as well as an architecture that makes it amenable to a wide variety of environmental problems. Theoretical underpinnings and capabilities are described in this paper and are illustrated with a multi-media example using a holistic approach to multi-media modeling that includes both feedforward and feedback processes among media. The holistic approach is compared to results that might arise from a more conventional approach using a set of single-media models coupled together in a feedforward-only fashion. The GEM is open-source and was developed to facilitate rapid model-building for a wide variety of environmental contamination problems. The authors encourage users to download and use the tool. Highlights: Overview of new, open-source, environmental fate and transport software, the Generic Environmental Model (GEM). Overview of several verification and validation examples illustrating wide variety of applications possible with GEM. Illustration of benefits of including both feedforward and feedback processes among media in multi-media example.